Corporate Social Responsibility dan Corporate Image: Survey pada Masyarakat Kota Denpasar - Habrianna, Ni Putu Sega Okta; Sisdyani, Eka Ardhani (E-Jurnal Akuntansi, 2024)
The company carries out corporate social responsibility (CSR) to improve the company's image. CSR is carried out with community support, environment, products and diversity. This research aims to determine the influence of corporate social responsibility on the corporate image of PT. BPR Lestari (survey of the people of Denpasar City). The sampling technique uses a non-probability sampling technique with a convenience sampling method. The data collection method used a questionnaire, from as many as 400 respondents. The analysis technique used is multiple linear regression using SPSS as an analysis tool. The results of the analysis show that CSR in the form of community support, environment, product and diversity has a positive effect on corporate image. Keywords: Corporate Social Responsibility; Community Support; Environment; Product; Diversity; Corporate Image.